1975
DOI: 10.1128/jcm.2.3.272-275.1975
|View full text |Cite
|
Sign up to set email alerts
|

Obligately Anaerobic Strains of Corynebacterium vaginale (Haemophilus vaginalis)

Abstract: Six obligately anaerobic strains of Corynebacterium vaginale (Haemophilus vaginalis) have been isolated and their characteristics studied. The reactions of the anaerobic strains, as well as of facultative strains tested under anaerobic conditions, are similar to the reactions previously reported for this species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Known as a facultative anaerobic microorganism, G. vaginalis was also described as fastidious, as it grew better at 37°C in complex media in an atmosphere with 5-10% of carbon dioxide (CO2) or in a candleflame extinction jar (Catlin, 1992;Cereija et al, 2013). Nevertheless, it was demonstrated that certain G. vaginalis strains are strict anaerobes (Malone et al, 1975). The cellular surface of G. vaginalis is covered with fimbriae, which are responsible for the attachment of G. vaginalis to vaginal epithelial cells (Scott et al, 1989;Onderdonk et al, 2016).…”
Section: Characteristics Of Gardnerellamentioning
confidence: 99%
“…Known as a facultative anaerobic microorganism, G. vaginalis was also described as fastidious, as it grew better at 37°C in complex media in an atmosphere with 5-10% of carbon dioxide (CO2) or in a candleflame extinction jar (Catlin, 1992;Cereija et al, 2013). Nevertheless, it was demonstrated that certain G. vaginalis strains are strict anaerobes (Malone et al, 1975). The cellular surface of G. vaginalis is covered with fimbriae, which are responsible for the attachment of G. vaginalis to vaginal epithelial cells (Scott et al, 1989;Onderdonk et al, 2016).…”
Section: Characteristics Of Gardnerellamentioning
confidence: 99%
“…Despite heavy growth in PYG or PYG-starch broth, none of the three reference strains of Bifidobacterium species, two reference strains of H. vaginalis, or the clinical isolates formed detectable levels of succinic acid in PYG or PYG-starch broth. However, since H. vaginalis may produce minor levels of succinate (9), like the bifidobacteria (6), analysis of volatile and nonvolatile end products would not necessarily separate H. vaginalis from bifidobacteria or possibly other species we have designated H. vaginalis-like.…”
Section: Discussionmentioning
confidence: 99%